The impact of advancing age on total serum IgE in asthmatic patient - Zeki, Yahya Yahya; Hussain, Majid K; Hussain, Mousa Kassim (AL-Kindy College Medical Journal, 2009)
Abstract The current study was conducted to assess the effect of advancing age on total serum IgE level in asthmatic patients. To this purpose, 90 asthmatic patients and 30 healthy individuals ( control group ) were enrolled. Asthmatic patients were categorized into four groups. Group A consisted of asthmatic patients (9) whose age was more than 20 and up to 30 y. Group B contained asthmatics (13) of age more than 30 and up to 40 y. Group C comprised those (23) of more than 40 and up to 50 y. Group D consisted asthmatic patients (45) of age more than 50 y. Total serum IgE level significantly changed in group D patients when compared with those of groups A and B. The linear regression analysis exhibited significant correlations for IgE (r=-0.65, P<0.001) with ages in asthmatic patients but not in healthy individuals